Strategies for Handling Non-Performing Qardhul Hasan Financing in Islamic Cooperatives: A Case Study of Baituttamkin Sharia Cooperative, Kediri Unit - Baiq Suhaera; Habibul Taqiuddin; Muhammad Yakub (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study investigates the causes and management strategies of non-performing Qardhul Hasan financing at the Baituttamkin Sharia Cooperative, Kediri Unit. The Qardhul Hasan scheme represents a non-profit, collateral-free financing model where members repay only the principal amount without profit sharing or service fees. However, its implementation frequently faces repayment problems due to members’ inability to fulfill obligations. Using a qualitative field research approach, data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman’s interactive model. The findings reveal two major factors contributing to non-performing financing: internal weaknesses, such as insufficient monitoring and weak assessment of member character, and external factors, including adverse economic conditions, business failure, and deliberate non-compliance by members. The cooperative’s handling strategies include home visits, friendly dispute resolution through musyawarah (deliberation), motivation and business mentoring, rescheduling, and recovery measures. These results emphasize that improving internal governance, member monitoring, and financial literacy can strengthen cooperative resilience and minimize future defaults.